Optogenetic stimulation shapes dendritic trees of infragranular cortical pyramidal cells - Gonda, Steffen; Köhler, Ina; Haase, André; Czubay, Katrin; Räk, Andrea; Riedel, Christian; Wahle, Petra (Frontiers in Cellular Neuroscience, 2023)
Spontaneous or experimentally evoked activity can lead to changes in length and/or branching of neocortical pyramidal cell dendrites. For instance, an early postnatal overexpression of certain AMPA or kainate glutamate receptor subunits leads to larger amplitudes of depolarizing events driven by spontaneous activity, and this increases apical dendritic complexity. Whether stimulation frequency has a role is less clear. In this study, we report that the expression of channelrhodopsin2-eYFP was followed by a 5-day optogenetic stimulation from DIV 5–10 or 11–15 in organotypic cultures of rat visual cortex-evoked dendritic remodeling. Stimulation at 0.05 Hz, at a frequency range of spontaneous calcium oscillations known to occur in the early postnatal neocortex in vivo until eye opening, had no effect. Stimulation with 0.5 Hz, a frequency at which the cortex in vivo adopts after eye opening, unexpectedly caused shorter and somewhat less branched apical dendrites of infragranular pyramidal neurons. The outcome resembles the remodeling of corticothalamic and callosal projection neurons of layers VI and V, which in the adult have apical dendrites no longer terminating in layer I. Exposure to 2.5 Hz, a frequency not occurring naturally during the time windows, evoked dendritic damage. The results suggested that optogenetic stimulation at a biologically meaningful frequency for the selected developmental stage can influence dendrite growth, but contrary to expectation, the optogenetic stimulation decreased dendritic growth.